B lymphocytes on the frontline of autoimmunity - Youinou, Pierre (Henry Stewart Talks, 2007)
Subpopulations of B cells, CD5-positive B cells, Marginal zone B cells, Follicular B cells, Pathogenic B cells, Cytokine-producing B cells, B cells and tolerance, BCR co-receptor molecules, Lipid rafts, BAFF in autoimmunity, The CD5 molecule in tolerance
Archived at 2018/05/31